Impact of COVID-19: Nursing challenges to meeting the care needs of people with developmental disabilities. Issue 1 (January 2021) - Desroches, Melissa L.; Ailey, Sarah; Fisher, Kathleen; Stych, Judith
Abstract: Background: People with developmental disabilities (DD) are a population at high-risk for poor outcomes related to COVID-19. COVID-19-specific risks, including greater comorbidities and congregate living situations in persons with DD compound existing health disparities. With their expertise in care of persons with DD and understanding of basic principles of infection control, DD nurses are well-prepared to advocate for the needs of people with DD during the COVID-19 pandemic. Objective: To assess the challenges faced by nurses caring for persons with DD during the COVID-19 pandemic and how the challenges impact people with DD. Methods: We surveyed 556 DD nurses, from April 6–20, 2020. The 35-item mixed-method survey asked nurses to rate the degree of challenges faced in meeting the care needs of people with DD. We analyzed responses based on presence of COVID-19 in the care setting and geographically. One open-ended question elicited challenges not included in the survey, which we analyzed using manifest content analysis. Results: Startlingly, nurses reported being excluded from COVID-19 planning, and an absence of public health guidelines specific to persons with DD, despite their high-risk status. Obtaining PPE and sanitizers and meeting social-behavioral care needs were the most highly ranked challenges. COVID-19 impacted nurses' ability to maintain adequate staffing and perform essential aspects of care. No significant geographic differences were noted. Conclusions: DD nurses must be involved in public health planning and policy development to ensure that basic care needs of persons with DD are met, and the disproportionate burden of COVID-19 in this vulnerable population is reduced.